If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -1(6x + -5) = -1 Reorder the terms: 4x + -1(-5 + 6x) = -1 4x + (-5 * -1 + 6x * -1) = -1 4x + (5 + -6x) = -1 Reorder the terms: 5 + 4x + -6x = -1 Combine like terms: 4x + -6x = -2x 5 + -2x = -1 Solving 5 + -2x = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -2x = -1 + -5 Combine like terms: 5 + -5 = 0 0 + -2x = -1 + -5 -2x = -1 + -5 Combine like terms: -1 + -5 = -6 -2x = -6 Divide each side by '-2'. x = 3 Simplifying x = 3
| 8b+5=22 | | h+5=6 | | 11x+7xy+2y+14z=15 | | 6X+7X=13 | | -28=-4(8+a) | | 4(2n-4)=7(n+3) | | r-/11/3=-7 | | (-4b)4= | | 16x^2+40x=-11 | | 3(t-2)+5t=4(2t+4)-9 | | 16x^2+40x+11=0 | | (-4b)b= | | -4x+4(7x+20)=-16 | | 452=6+50d | | X+46=73 | | 5=5/8(4)-3 | | 4-(2y+5)= | | .75x-.25(10-x)=.89(10) | | 4x+4(-6x-4)=16 | | 0.3x-0.3y-0.4z=0.5 | | .75x+.25(10-x)=.89(10) | | g(x)=sqrt(6x+2) | | 4+4h=7.25 | | -2a(-9ax-8)= | | -1/8c=12 | | 4x-24-16=16 | | 10x-3=6-4 | | H/4=7.25 | | 2/3x=10x=15 | | 0.3(4g+6)=0.2(6g-9) | | H(4+h)=7.25 | | 3052.08=4/3*3.14r³ |